Factors influencing employees’ performance in islamic bank: case study at Bank Islam Malaysia Berhad (BIMB) and Bank Muamalat in Perak / Jabariah Ishak and Nur Syamimi Abd Aziz - Ishak, Jabariah; Abd Aziz, Nur Syamimi (2014)
Employee is a backbone for any organization and the success or failure of the organization depends on the employee performance. So, management should play a vital role to implement strategies to improve their employees’ performance. The purpose of this study is to find out the factors influencing employees’ performance in Islamic bank. The sample of the study is 226 employees of BIMB and Bank Muamalat at Perak have been chosen using stratified random sampling. Reliability analysis, correlation analysis and regression analysis were applied to gather the result. The results found that better education, work environment, communication skills and motivational factors has significant relationship with employees’ performance. The recommendations for future research also have been discussed